Influence of the Mountain Pine Beetle disturbance on large wood dynamics and channel morphology in mountain streams - Marston, Bryce Kendrick (Kansas State University, 2017)
Disturbance regimes are important determinants of both terrestrial and aquatic ecosystem structure and function. Disturbances may linger in the landscape and lag temporally, influencing stream ecosystem form and function for decades, if not centuries. The recent enhanced Mountain Pine Beetle (MPB) infestation in pine forests of the Rocky Mountain region has resulted in extensive tree mortality, producing the potential for significant increases in carbon supply to stream channels. To better understand MPB impacts on in-stream large wood (LW), a census was conducted in 30 headwater streams within the Medicine Bow National Forest in south-central Wyoming, across the temporal spectrum from early- to late-stage MPB-infestation. A subset of those streams exhibiting mean conditions at each level of infestation was surveyed to determine any significant differences in channel morphology or aquatic ecosystem function. Results indicate that wood loads related to the MPB-infestation significantly increase with time since initial infestation. However, even in late-stage infestation streams, many of the fallen MPB-killed trees are bridging across the channels and have yet to break and ramp down sufficiently enough to enter between the channel margins. Wood loads will continue to increase as more trees fall and bridging pieces decompose, break and then enter the channel. Measurable increases in the amount of LW with time since initial beetle infestation have both positive and negative effects on channel form and function. Although forest MPB-infestation has peaked in the study area, streams are still early on a curve of rapidly increasing wood loads that are beginning to affect streams and have the potential to dramatically increase the carbon base of regional stream ecosystems.
Keywords: Geography; Fluvial geomorphology; Geomorphology; Water resource management